IMPLEMENTASI PENDIDIKAN DAN PELATIHAN DALAM MENINGKATKAN KOMPETENSI GURU (STUDI KASUS PADA UPT SMP NEGERI 2 DUAMPANUA KABUPATEN PINRANG) - Muh Nur Rasyid; Andi Nurqalbiani (Jurnal Ilmu Manajemen Profitability, 2020)
The purpose of this study is to analyze the training needs, to find out in setting training objectives, to find out the training curriculum development, to find out the preparation of education and training, to know the implementation of education and training, to find out training evaluation in improving teacher competence. This type of research is descriptive qualitative, data collection techniques used observation, interviews, and documentation. Sources of data are the Principal, Deputy Principal and teachers at UPT SMP Negeri 2 Duampanua. The results of this study indicate that the implementation of education and training in improving teacher competence in UPT SMP Negeri 2 Duampanua is carried out through 6 stages of education and training which include; (1) training needs analysis (Taining Need Assessment), (2) setting training objectives, (3) curriculum development, (4) preparation of training, (5) implementation of education and training, (6) evaluation, basically it has been done quite well it's just that there are deficiencies in terms of evaluation, the training evaluation conducted by UPT SMP Negeri 2 Duampanua is not sustainable and the implementation is only at the training venue, and is not accompanied by follow-up on how the application of the capabilities that have been obtained in the effort to utilize those capabilities is really controlled professionally.